2019
DOI: 10.1101/588871
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Polymorphisms in the vitamin D system and mortality - The Tromsø study

Abstract: Background and objectiveVitamin D deficiency is associated with diabetes, cancer, immunological and cardiovascular diseases as well as increased mortality. It has, however, been difficult to show a causal relation in randomized, controlled trials. Mendelian randomization studies provide another option for testing causality, and results indicate relations between the serum 25hydroxyvitamin D (25(OH)D) level and some diseases, including mortality. We have from the Tromsø Study in 2012 published non-significant r… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
2
1

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 47 publications
(47 reference statements)
0
2
1
Order By: Relevance
“…To extract this detailed information from all included studies caused the rather long duration from the underlying systematic search to reporting the results. However, no conflicting results were found when comparing the outcomes of our study to recently published data [ 121 , 122 , 140 , 141 , 142 , 143 , 144 , 145 , 146 , 147 , 148 , 149 ]. The focus of recently published data remains in the same gene’s polymorphisms: GC, CYP2R1, VDR, CYP24A1, and CYP27B1.…”
Section: Discussioncontrasting
confidence: 78%
See 2 more Smart Citations
“…To extract this detailed information from all included studies caused the rather long duration from the underlying systematic search to reporting the results. However, no conflicting results were found when comparing the outcomes of our study to recently published data [ 121 , 122 , 140 , 141 , 142 , 143 , 144 , 145 , 146 , 147 , 148 , 149 ]. The focus of recently published data remains in the same gene’s polymorphisms: GC, CYP2R1, VDR, CYP24A1, and CYP27B1.…”
Section: Discussioncontrasting
confidence: 78%
“…Furthermore, it has been shown that C2 myotubes and primary rat muscle fibers express megalin and cubilin receptors, which enable endocytosis of DBP [ 120 ]. Studies on megalin and cubilin published after the search closing date of this systematic review did not reveal new findings [ 121 , 122 ]. In addition to the previously mentioned functional polymorphisms in the GC gene, there are also intron-located SNPs, which were found to be associated with vitamin D status, whereas the underlying mechanism remains unclear.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation